Solid slow-release carbon source assembled microbial fuel cell for promoting superior nitrogen removal in an aerobic granular sludge bioreactor. (1st January 2023) - Zhao, Chuanfu; Wang, Yibing; Meng, Shuangyu; Zhang, Wenhao; Zhang, Xinwen; Yan, Liangguo; Wei, Qin; Wei, Dong
Abstract: Although the coupling process of microbial fuel cell (MFC) and activated sludge is widely used for organic matter removal and electric energy recovery, the problem of high effluent nitrate still exists due to the lack of influent carbon source. Herein, a poly (butanediol succinate) (PBS) assembled MFC was established in an aerobic granular sludge (AGS) bioreactor for simultaneous promoting nitrogen removal and electricity generation. Compared to AGS-Control group, the total inorganic nitrogen (TIN) and COD removal efficiencies of AGS-MFC group were improved to 84.3 ± 2.6% and 93.5 ± 0.5% after 100-days operation. The average output voltage and the maximum power density of the MFC module were 223.7 mV and 59.6 mW/m 2, respectively. Through high-throughput sequencing analysis, Thauera -related denitrifying bacteria had the highest relative abundances (20.0% and 31.4%) in both bioreactors. The relative abundance of Nitrosomonas -related ammonia oxidizing bacteria (AOB) in AGS-MFC (1.8%) was enriched than AGS-Control (1.1%). In MFC module, Thauera (16.2%) with denitrification and power generation was dominant in anodic biofilms under PBS enhancement. This study provides scientific basis for the application of submersible MFC enhanced deep nitrogen removal under aerobic conditions. Graphical abstract: Image 1 Highlights: A PBS assembled MFC was successfully established in an AGS bioreactor. AGS-MFC system significantly reduced effluent TIN under PBS enhancement. Thauera had the highest relative abundances in both AGS bioreactors.